REPRESJE ZE STRONY WŁADZ PAŃSTW KOMUNISTYCZNYCH WOBEC OSÓB DUCHOWNYCH – ZARYS PROBLEMU - Kaczmarek, Piotr (Społeczeństwo, 2026)
Communism was one of the three major totalitarian systems that, in the twentieth century, came to dominate primarily the Central and Eastern regions of Europe. One of its defining features was atheism and its struggle against religion – especially Christianity, whose adherents constituted a significant majority of the European continent. To achieve this goal, the communists primarily targeted Church hierarchs and other members of the clergy, persecuting them and subjecting them to severe repression. This article presents examples of some of the most well-known cases of repression against clergy by the authorities of communist states. It addresses, among other topics, the trial of Archbishop Jan Cieplak of Mohilev in 1923, as well as the issue of repression against individual clergymen in Central and Eastern European countries other than the Union of Soviet Socialist Republics.